Postcapitalist Precarious Work and Those in the ‘Drivers’ Seat: Exploring the Motivations and Lived Experiences of Uber Drivers in Canada - Peticca-Harris, Amanda; deGama, Nadia; Ravishankar, M. N. (Organization, 2020)
In this inductive, qualitative study, we observe how Uber, a company often hailed as being the poster-child of the sharing economy facilitated through a digital platform may also at times represent and reinforce postcapitalist hyper-exploitation. Drawing on the motivations and lived experiences of 31 Uber drivers in Toronto, Canada, we provide insights into three groups of Uber drivers: (1) those that are driving part-time to earn extra money in conjunction with studying or doing other jobs, (2) those that are unemployed and for whom driving for Uber is the only source of income, and (3) professional drivers, who are trying to keep pace with the durable digital landscape and competitive marketplace. We emphasize the ways in which each driver group simultaneously acknowledges and rejects their own precarious employment by distancing techniques such as minimizing the risks and accentuating the advantages of the driver role. We relate these findings to a broader discussion about how driving for Uber fuels the traditional capitalist narrative that working hard and having a dream will lead to advancement, security and success. We conclude by discussing other alternative economies within the sharing economy.
https://repository.lboro.ac.uk/articles/Postcapitalist_precarious_work_and_those_in_the_drivers_seat_Exploring_the_motivations_and_lived_experiences_of_Uber_drivers_in_Canada/9503267/files/17130035.pdf